Fructooligosaccharides (FOS) differentially modifies the in vitro gut microbiota in an age-dependent manner - Mahalak, Karley K.; Firrman, Jenni; Narrowe, Adrienne B.; Hu, Weiming; Jones, Steven M.; Bittinger, Kyle; Moustafa, Ahmed M.; Liu, LinShu (Frontiers in Nutrition, 2023)
Introduction Fructooligosaccharides (FOS) are well-known carbohydrates that promote healthy gut microbiota and have been previously demonstrated to enhance levels of Bifidobacterium and Lactobacillus. Its bifidogenic properties are associated with positive health outcomes such as reduced obesity and anti-inflammatory properties, and, therefore, is in use as a prebiotic supplement to support healthy gut microbiota. However, the gut microbiota changes with age, which may lead to differential responses to treatments with prebiotics and other dietary supplements. Methods To address this concern, we implemented a 24-h in vitro culturing method to determine whether FOS treatment in three different adult age groups would have a differential effect. The age groups of interest ranged from 25 to 70 years and were split into young adults, adults, and older adults for the purposes of this analysis. Metagenomics and short-chain fatty acid analysis were performed to determine changes in the structure and function of the microbial communities. Results These analyses found that FOS created a bifidogenic response in all age groups, increased overall SCFA levels, decreased alpha diversity, and shifted the communities to be more similar in beta diversity metrics. However, the age groups differed in which taxa were most prevalent or most affected by FOS treatment. Discussion Overall, the results of this study demonstrate the positive effects of FOS on the gut microbiome, and importantly, how age may play a role in the effectiveness of this prebiotic.